2010
DOI: 10.1007/s10530-010-9848-y
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of ant eradication efforts on offshore islets in the Hawaiian Archipelago

Abstract: Invasive species eradication and control are considered vital components of the conservation, restoration, and management of many native ecosystems. Invasive ants, which are notoriously difficult to eradicate, can cause catastrophic changes in ecosystems and are aggressive colonists. Here we report the eradication and control of two widely distributed invasive ants and subsequent unanticipated effects on arthropod and avian communities. We used a paired experimental design that included 1 year of baseline data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Hoffmann (2010) reported a complete recovery of native ants after eradication of P. megacephala in northern Australia, whereas Plentovich et al (2011) observed colonization by other invasive species after eradication of P. megacephala on small offshore islets in the Hawaiian archipelago. Natural succession and re-colonization, however, is often hampered by the severity of modification inflicted by the invader.…”
Section: Mitigation/eradication/restorationmentioning
confidence: 99%
“…Hoffmann (2010) reported a complete recovery of native ants after eradication of P. megacephala in northern Australia, whereas Plentovich et al (2011) observed colonization by other invasive species after eradication of P. megacephala on small offshore islets in the Hawaiian archipelago. Natural succession and re-colonization, however, is often hampered by the severity of modification inflicted by the invader.…”
Section: Mitigation/eradication/restorationmentioning
confidence: 99%
“…An additional explanation for our finding that RIFAs did not influence fence lizard survival is that Amdro, although largely targeted to control RIFAs, can reduce native ant and orthoptera populations (Plentovich et al. ). Ants comprise a large proportion of the fence lizard diet (approximately 80% in juveniles), though other invertebrates (e.g., Orthoptera) make a considerable contribution (Hamilton and Pollack , DeMarco et al.…”
Section: Discussionmentioning
confidence: 93%
“…], Hawai'i [Plentovich et al . ]), which may be more susceptible to effects of invasive species than continental ecosystems (Simberloff ). Only one published study has investigated effects of A. gracilipes on invertebrate communities on mainlands, and it found no significant effect of A. gracilipes on the abundance or richness of ground invertebrates (Hoffmann & Saul ).…”
Section: Results Of the Generalized Linear Mixed Models Of The Likelimentioning
confidence: 99%